A Correlational Study on Subtitled Movie Watching and Vocabulary Mastery among EFL Students - Muhammad Arif Musthofa; Sudar; Sri Widodo (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study investigates the relationship between students’ habit of watching English movies with subtitles and their vocabulary mastery in an EFL context, addressing the limited evidence on how informal audiovisual exposure functions in natural learning settings. A quantitative correlational design was employed, involving 27 students selected through total sampling. Data were collected using a 20-item Likert-scale questionnaire to measure viewing habits (Cronbach’s α = .763) and a 25-item multiple-choice vocabulary test to assess vocabulary mastery. The results revealed a positive but weak and statistically non-significant correlation (r = .115; p = .568), indicating that frequent exposure to subtitled movies is not a strong predictor of vocabulary mastery. These findings suggest that informal exposure alone may not lead to substantial vocabulary development without sufficient cognitive engagement. The study highlights the importance of learner involvement and supports the view that the effectiveness of audiovisual input depends on how learners process the input rather than the exposure itself. This study contributes to the understanding of informal language learning by emphasizing the gap between perceived and actual learning outcomes in natural contexts.